Supernatural Forces and their role in the “Haft Lashkar” - mohammad fuladi; zahra gholami (نثرپژوهی ادب فارسی, 2019)
One of the motifs of epic and mythological stories is the supernatural forces’ intervention made in the form of supernatural aids from God in support of a hero. In mythology, the inability of a hero is offset by supporting forces or supernatural forces. A mythical hero, praying and seeking help from God, fights a battle against an anti-hero, a demon, a dragon, and wins the victory over all his enemies with seeking help from God. The hero of the epic has a strong connection with the divine and supernatural forces, which often occurs in the form of association with the gods and predictions of his destiny. The predictions usually are made through seeing dreams, hearing the voice of an invisible speaker (soroush), the astronomers, spiritual leaders, fairies and Simurgh. And the association of the hero with God and his benefitting from the gods’ support sometimes directly takes place. Magical objects, ceremonial armaments and special armaments for killing dragons, such as the ox-headed mace and the armaments that are memorials from heroes' ancestors, including armlet gem, realistic and mythological animals, and supernatural beings such as fairies and demons and natural forces such as wind come to help the hero. Here in, referring to the narrative scroll of “Haft Lashkar” I have tried to examine analytically and descriptively the supernatural powers that are supporting and helping a hero.